KELEMBAGAAN HUTAN DESA DI DESA LONCA KECAMATAN KULAWI KABUPATEN SIGI - Mondo, Andro Jamal; Akhbar, Akhbar; Golar, Golar (Jurnal Warta Rimba, 2016)
Village Forest as The state forest area which is in village administration area that managed by economic organization in the village, it gives public service that relates to the arrangement and management of the forest. To prepare and to watch the implementation of the village forest management, the society and the official government of Lonca village by the meeting that held on 6-7 November 2011, had established the Organization of Lonca Village Forest Management. The establishment of the organization is to support the success of Village Forest in the Loca village Kulawi subdistrict Sigi district. The problem of the research was what the roles of village Forest Organization in supporting the development of the Village Forest. The research was conducted on May up to the month of July 2015, that located in Lonca village Kulawi subdistrict Sigi district. The data gathering was done by observing and interviewing by using questionnaire. The research method applied descriptive analysis, that including role analysis (4R) and analysis method of frequency distribution (modus), it was the rate/number that frequently revealed in the series of numbers/numbers list. The result of the research found that the all organizations that related to the planning of village Forest Management worked together and did the jobs especially the Organization of Village Forest Management. Otherwise, the Planning program of Village Forest Management in Loncavillage had not worked optimally, it caused of no program of work that owned, so what would be done by the organization of village Forest Management was not clear yet.Keywords: Organization, Village Forest, Lonca village